A Lei 14.023/07 e os investimentos em educação fundamental e saúde nos Municípios Cearenses: uma análise no período 2006-2010 - Garcia, Felipe Gomes (2012)
The study it investigates the effect of the change in the rules of the calculation of the quota has left of the ICMS on the investments of the pertaining to the state of Ceará city halls, in the areas of basic education and health. A panel with 171 pertaining to the state of Ceará cities with annual data between 2006 and 2010 gave support to the esteem of econometrical models that had allowed to evidence a positive and increasing impact on the evolution of the views of resources to the above-mentioned areas to break the date of promulgation of Law 14.023/07. Controlling for the ICMS transferred to the cities, the results suggest the effectiveness of the cited Law in extending the investments in these social areas.